Penggunaan Metode Simulasi untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen - Rudolf Weindra Sagala; Jhoni Lagun Siang (Pascasarjana IAKN Manado, 2022)
This classroom action research discusses efforts to improve student learning outcomes through the use of discussion methods. The problem in this study is that the PAK learning process in class VII rarely or less uses the simulation method. This causes various problems in the classroom, including: lack of interest in student learning, low student learning outcomes. The benefit of this research is that it can find various obstacles as well as solutions, regarding the use of the simulation method as an effort to improve PAK learning outcomes while motivating teachers to be skilled in choosing and using methods in learning to attract students' interest in learning. The results showed that by using the simulation method there was a change in students, namely students became interested, and active and motivated so as to improve student learning outcomes. Based on the results of the study, it is recommended that teachers in teaching must be able to determine and use appropriate methods